2017
DOI: 10.1007/s10661-017-5873-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic parameters in monitoring cytogenotoxic effects of fertilizer in Allium cepa L.

Abstract: The present investigation was done to assess cytomorphologic parameters as indicators of genotoxicity as it is a simpler method and could be suggested for rapid screening of the vast range of agrochemicals used all over the world. The excessive and indiscriminate use of agrochemicals is responsible for increasing the level of pollutants in the soil environment resulting in cellular and molecular damage to the plants. The cellular damage caused manifestation of the resulting oxidative stress due to pollutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The effects of fertilizers on chromosomal behaviors using plant models have also been reported in other studies [38,39]. Genotoxic and chromosomal abnormality endpoints from plant studies remains relevant for toxicity and risk assessment of agrochemicals, including fertilizer [23]. Therefore, our findings may suggest the need to investigate the cytological aberrations and other mutagenic effects of fertilizers using mammalian experimental models.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The effects of fertilizers on chromosomal behaviors using plant models have also been reported in other studies [38,39]. Genotoxic and chromosomal abnormality endpoints from plant studies remains relevant for toxicity and risk assessment of agrochemicals, including fertilizer [23]. Therefore, our findings may suggest the need to investigate the cytological aberrations and other mutagenic effects of fertilizers using mammalian experimental models.…”
Section: Discussionsupporting
confidence: 78%
“…Kumar and Sana demonstrated various chromosomal abnormalities in plants after exposure to high concentrations of fertilizers [37]. Similarly, Verma et al investigated the genotoxic effects of nitrogen fertilizers in plants and concluded that nitrogen fertilizer induced chromosomal aberrations, including fragmentation, bridges, and disorientations [23]. The effects of fertilizers on chromosomal behaviors using plant models have also been reported in other studies [38,39].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A significant decrease in MI and increase in abnormality percentage compared to the control was observed with increasing duration of the ammonium nitrate treatment (Verma and Srivastava 2017). Chromosomal aberrations like stickiness, fragmentation, precocious movement, bridges and disorientations were observed in varying frequencies.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Timentioning
confidence: 86%
“…El-Din et al (2009) observed mutagenic potentialities of N fertilizers in animals also. Some reports showed the cytogenotoxic effects of fertilizers on Vicia faba and Allium cepa (Oney and Tabur 2013, Verma et al 2016, Verma and Srivastava 2017. A. cepa root tip bioassay has been considered as a classical test system to assay the chromosomal aberrations and to indicate the presence of mutagenic chemicals due to its kinetic characteristics of proliferation and possession of chromosomes suitable for cytotoxic study (Barberio et al 2011, Sharma and Vig 2012, Pathiratne et al 2015, Fatma et al 2018.…”
mentioning
confidence: 99%